2017
DOI: 10.7567/jjap.56.081701
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of the reflection spectrum of the polymer-stabilized cholesteric liquid crystal on the length of the diacrylate and monoacrylate reactive mesogen molecules

Abstract: We investigated the dependence of the reflection spectrum of the polymer-stabilized cholesteric liquid crystal (PSCLC) on the length of the diacrylate and the monoacrylate reactive mesogen (RM) molecules. The reflection bandwidth, the reflection center wavelength, and the peak reflectance of the PSCLC with a short diacrylate and a monoacrylate RM were similar to those of the pure cholesteric liquid crystal (CLC). When a longer diacrylate RM was used, the specular reflection bandwidth was broadened and the refl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…In the planar state, the sample’s transmittance at 560 nm decreased from 24.8% at 1% content to 11.1% at 5%. This is attributed to the fact that light scattering is enhanced due to the increased density of the polymer network, with a consequent declining transmittance . However, the transmittance of the focal cone state shows a trend of decreasing and then increasing and reaches a minimum value of 3.2% at an HDDA content of 3%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the planar state, the sample’s transmittance at 560 nm decreased from 24.8% at 1% content to 11.1% at 5%. This is attributed to the fact that light scattering is enhanced due to the increased density of the polymer network, with a consequent declining transmittance . However, the transmittance of the focal cone state shows a trend of decreasing and then increasing and reaches a minimum value of 3.2% at an HDDA content of 3%.…”
Section: Resultsmentioning
confidence: 99%
“…This is attributed to the fact that light scattering is enhanced due to the increased density of the polymer network, with a consequent declining transmittance. 40 However, the transmittance of the focal cone state shows a trend of decreasing and then increasing and reaches a minimum value of 3.2% at an HDDA content of 3%. Therefore, it can be concluded that the CR of samples a1−a5 shows a trend of increasing and then decreasing according to the above definition of CR, as shown in Figure 3c.…”
Section: Characterizationmentioning
confidence: 94%